Natural foci of tick-borne encephalitis in central Europe and the relationship of the incidence of Ixodes ricinus to original ecosystems - Minár, J (Central European journal of public health, 1995)
Based on reports of the national epidemiological service on tick-borne encephalitis (TBE) morbidity in 1953-1987, data in the literature, and results of the author's own field research on the occurrence of the common tick, Ixodes ricinus, foci of this disease have been identified on the territory of Czechoslovakia. In Bohemia a significant focus of TBE in the Central Bohemian Region is located in the Krivoklát area with forests and in the Berounka, mid-Vltava, and lower-Sázava river basins, in the Brdy area and the Czech Karst continuing southwards via the Vltava basin to foci in the South Bohemian region in the districts of Písek and Ceské Budĕjovice and west of the Berounka river basin to a focus in the central part of the West Bohemian region. In the North Bohemian and East Bohemian regions only smaller isolated foci of TBE were detected. In Moravia foci of TBE are in the districts of Opava and Bruntál in the North Moravian region and in the central and southern areas of the South Moravian region. The foci in Bohemia are isolated from foci in neighboring countries, those of Moravia are connected with foci in Poland and Austria. On the territory of the Czech Republic foci of TBE are found in localities of pristine oakwood agglomerations. Original beechwood agglomerations even when located below the upper limit of occurrence of the common tick, i.e. less than 700 meters above sea level, do not offer favourable conditions for this arthropod and they do not harbour natural foci of TBE.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Animals; stromy; ekosystém; Česká republika; Ecosystem; Incidence; klíšťata; zvířata; klíšťová encefalitida; Ticks; Trees; incidence; Czech Republic; Encephalitis, Tick-Borne